Ваконіми села Піщаний Брід Добровеличківського району Кіровоградської області - Громко, Тетяна; Hromko, Tetiana (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті подано говірковий матеріал однієї з груп онімної лексики села Піщаний Брід. Ваконіми скласифіковані за мотиваційною специфікою номінації: зовнішніми особливостями тварини, її норовом та поведінкою, періодом народження, ставленням власника до неї тощо. З’ясовано, що клички бикам і коровам можуть надавати господарі та інші люди, пов’язані з доглядом за ними, а також встановлені оніми, які змінювалися від народження тварини упродовж всього її життя. Серед проаналізованих ваконімів виділені ті, твірною основою яких стали людські імена, прізвища, патроніми, прізвиська, у них є і вказівка на національність господарів, однак найчастіше вживаними виявилися клички, що вказують на масть, норов та характер тварин. The article considers the dialectal material presenting a group of onymic vocabulary, defined as vaconyms (the case study of the vaconyms of the village Pishchanyi Brid, Dobrovelychkivskyi district, Kirovograd region). The vaconyms are classified according to the specific motivational peculiarities and tendencies of giving names to animals. The author suggests classification of these tendencies according to the external/appearance features of an animal, its behavior and temper, the period of birth, the owner’s attitude to the animal and other criteria. It has been revealed that in the majority of cases the names to the bulls and cows are given by their owners and other people caring for them. The study identified the onyms that have been changing since the birth and throughout the animal's life. Among the analyzed vaconyms there have been selected those which were created on the basis of human names, surnames, patronymics, nicknames. The author claims that some of the vaconyms indicate even to the nationality of their owners, but those indicating color, temper and nature of animals are the most frequently met.
Vaconyms of the Village Pishchanyi Brid of the Dobrovelychkivskyi District, Kirovograd Region.
Keywords: методика вивчення говорів; говірка; діалектне явище; вакoнім; словник говірки; methods of studying dialects; dialect; dialectal phenomenon; vaconym; dictionary of dialects